PENGARUH PENGGUNAAN MEDIA AMPLOP BAPER TERHADAP KEMAMPUAN MENYUSUN KALIMAT BAHASA MANDARIN SISWA XII MIA 1 SMAN 8 SURABAYA - Purnamasari, Panca (Jurnal Bahasa Mandarin, 2017)
In learning Chinese in class XII SMAN 8 Surabaya, students experience many difficulties, especially in composing the sentences. To overcome the learning difficulties experienced by students, researcher used “baper” envelope media. This research has three problem formulations, first on how application of “baper” envelope media usage in learning to compose Chinese sentences of students class XII MIA1 SMAN 8 Surabaya academic year 2016/2017, second on how the effect of “baper” envelope media usage on the ability to compose Chinese sentences of Students class XII MIA1 SMAN 8 Surabaya academic year 2016/2017, third on how the response of students class XII MIA1 SMAN 8 Surabaya academic year 2016/2017 on the ability to compose Chinese sentences by using “baper” envelope media. This research is experimental research with quantitative approach in descriptive method. This study was conducted during four meetings. Twice in the control class (using the lecture method), and twice in the experimental class (using “baper” envelope media). Class XII MIA8 is the control class and class XII MIA1 is the experimental class. Based on the calculation of learning outcomes of students in control and experimental classes, obtained the result t0 = 1874 and = 75, it is known that the value = 0,05 = 2,00 shows t is greater than t table (2.00 <1874). It means value of t0 significant. Thus, from the analysis of student learning outcomes proved that there is a significant difference between the ability to compose Chinese sentences in experimental students using “baper” envelope media with control class students using power point media. It is proven that “baper” envelope media can improve the ability to compose Chinese sentences to students. Based on the result of questionnaire analysis, 71.5% students stated that learning of composing Chinese sentences with “baper” envelope media is a new thing for the respondents, 75.8% students stated the model of composing the sentence with “baper” envelope media made it easier for them to read the Chinese language, 88.4% students stated that the use of “baper” envelope media can motivate in learning Chinese, 81.0% students stated the benefits of using “baper” envelope media is easy to understand in learning to compose Chinese sentences, 7% students said this “baper” envelope media reviewed them to be more creative in learning Chinese, 90.5% students stated the color of “baper” envelope media is very interesting, 90% students stated that the “baper” envelope media did not make them felt bored in learning Chinese, 89% students expressed learning using “baper” envelope media can keep the closeness between classmates, 86.8% students stated that the quality of “baper” envelope media is quite good in Chinese learning, 85.7 students stated that learning to compose the sentences using envelope “baper” media is very impressive. From the result of questionnaire of students response, it can be concluded that “baper” envelope media in Mandarin learning on the ability to compose Mandarin sentences is very effective. This is because learning by using “baper” envelope media is more interesting and fun so that it can help students on the ability to compose Chinese sentences. ?? ??“BAPER”?????????????????????? XII MIA 1 SMAN 8 SURABAYA??2016/2017 ?? ?Panca Purnamasari NIM ?13020774058 ? ??????? ?? ?????? ?? ??????? ?? ?Dr.Urip Zaenal Fanani?M.Pd? ?? ?2017? ??????????“Baper”???? ?????XII SMAN 8??????????????????????????????????????????“baper”?????????????????????????“baper”??????????????????XII MIA1 SMAN 8????2016/2017?????“baper”???????????????????XII MIA1 SMAN 8????2016/2017???????????XII MIA 1 SMAN 8????2016 / 2017?????“baper”?????????????????????????????????. ???????????????.????????????????????????“baper”?????? ? XII MIA 8??????XII MIA 1 ????. ?????????????????, ????t0 = 1874?db = 75????to_s = 0,05 = 2,00??t??t??2.00 <1874??????t0??????????????????????????“baper”???????????????????????????????????? ??“??”????????????????????????????????71.5????????“baper”?????????????????????????75.8?????“baper”??????????????????????????88.4?????????“baper”?????????????81.0????????“baper”??????????????????????7???????“baper “?????????????????????90.5??????“baper”????????????90???????“baper”???????????????????89??????????“baper”???????? 86.8???????“??”???????????????????85.7??????????“baper”??????????????????? ??????????????????????“baper”???????????????????????????“baper”?????????????????????????????